1995
DOI: 10.1002/anie.199518901
|View full text |Cite
|
Sign up to set email alerts
|

C4S: A Bridging Bis(dithiolato) Ligand for the Preparation of Semiconducting Inorganic Polymers

Abstract: Planar and highly polarizable, the dianionic thiocarbon 1 reacts with metal salts to give inorganic polymers like [Cu2C4S6] and [NiC4S6] with semiconductor properties. The Ni coordination polymer forms a one‐dimensional ribbonlike strand of edgesharing square‐planar complexes such as 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Multi-thiobenzene based ligands have been used to coordinate with different metal ions to form a number of semiconducting coordination polymers. 55 Kitagawa, H. et al reported the first porous and conductive MOF from Cu(II) and pdt (pdt = 2,3-pyrazinedithiolate) building blocks through both Cu-S and Cu-N bonds in 2008. 56 This MOF showed a conductivity of 6 × 10 −4 S/cm at 300 K, which was attributed to a bistability between Cu I [Cu III (pdt) 2 ] and Cu II [Cu II (pdt) 2 ] states.…”
Section: Electro- and Photo-active Mofs For Energy Conversion And Stomentioning
confidence: 99%
“…Multi-thiobenzene based ligands have been used to coordinate with different metal ions to form a number of semiconducting coordination polymers. 55 Kitagawa, H. et al reported the first porous and conductive MOF from Cu(II) and pdt (pdt = 2,3-pyrazinedithiolate) building blocks through both Cu-S and Cu-N bonds in 2008. 56 This MOF showed a conductivity of 6 × 10 −4 S/cm at 300 K, which was attributed to a bistability between Cu I [Cu III (pdt) 2 ] and Cu II [Cu II (pdt) 2 ] states.…”
Section: Electro- and Photo-active Mofs For Energy Conversion And Stomentioning
confidence: 99%
“…Steamed in the water air, the turpentine from the pine in the overflow. Carbonic sulfide polymers are the newly inorganic compounds,which possess the functions of molecular self-assembly, semiconductors,non-linear optical and active chemical intermediates [3][4]. After resin curing, the crisp, loss of mobility, to achieve the purpose of fat-free.…”
Section: A Influence Of Sulfur Additionmentioning
confidence: 99%
“…The internal atomic positions as well as the length of cell vector a were then relaxed until convergence in the forces was achieved to within 0.001 eV per Å. mentioned in the Introduction. [22][23][24][25][26] While none of the known [Ni(C x S y )] n compounds were crystalline, and their structures therefore could not be determined by X-ray crystallography, they are generally presumed to be one-dimensional polymers formed by alternating Ni 2+ and C x S y…”
Section: Computational Detailsmentioning
confidence: 99%
“…19 Hybrid networks containing Cu + , Cu 2+ , or Ag + and 1,4-benzenedithiolate 20 or Fe 2+ , Ni 2+ , or Cu 2+ and 1,2,4,5-benzenetetrathiolate 21 are semiconducting, but they are also all amorphous. [22][23][24][25][26] The compound formed between Pb 2+ and benzenehexathiolate, [Pb 3 (C 6 S 6 )] n , is crystalline with a three-dimensional network structure and is semiconducting. 27,28 Several conjugated organic systems containing multiple cyano groups (tetracyanoethylene, TCNE; 7,7,8,8-tetracyanoquinodimethane, TCNQ; 1,2,4,5-tetracyanobenzene, TCNB; N,N 0 -dicyanoquinonediimine DCNQI) have been used to form networks with various metal ions, and several of those are electrically conducting.…”
Section: Introductionmentioning
confidence: 99%